2010
DOI: 10.1038/ijir.2010.29
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ preference in the treatment of erectile dysfunction: a critical review of the literature

Abstract: The increase in the number of safe and effective ED treatments highlights the importance of patients' preference when choosing a therapeutic option. Several studies assessing these preferences are now available in published literature. This article aims to review and discuss the studies on patients' preference and the data concerning the reasons for preference for one PDE-5 inhibitor over another. A PubMed search was conducted for manuscripts published within the last 10 years containing the search items ED, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Several sponsored and independent nonsponsored studies have investigated whether patients/couples prefer one PDE5 inhibitor over others after patients tried sildenafil, vardenafil, and/or tadalafil over a reasonably long period of time. A recent review of the literature from 2000 to 2010 on this topic concluded that preferences of the patients/ couples were the following [71]:…”
Section: Preference Studies Between Marketed Pde5 Inhibitorsmentioning
confidence: 99%
“…Several sponsored and independent nonsponsored studies have investigated whether patients/couples prefer one PDE5 inhibitor over others after patients tried sildenafil, vardenafil, and/or tadalafil over a reasonably long period of time. A recent review of the literature from 2000 to 2010 on this topic concluded that preferences of the patients/ couples were the following [71]:…”
Section: Preference Studies Between Marketed Pde5 Inhibitorsmentioning
confidence: 99%
“…Erectile dysfunction (ED) is the consistent inability of a man to achieve or maintain penile erection sufficient for sexual activity . Common causes of ED include aging and endothelial dysfunction associated with behaviors such as smoking or conditions including type 2 diabetes mellitus (T2DM), hypertension (HTN), and other cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Additionally, the greater ease of planning and convenience findings were consistent with prior research on patient preferences showing that a majority of patients preferred tadalafil over either sildenafil or vardenafil; patients perceived that tadalafil allowed them greater sexual spontaneity. 30 Moreover, while BPH/LUTS improved significantly with either tadalafil or tamsulosin monotherapy, relative to a placebo, only tadalafil significantly improved ED symptoms. 17 Therefore, the collective evidence suggests that men may not only be more satisfied with the efficacy of tadalafil treatment for BPH with (or without) ED but they may also perceive this treatment to be more convenient than some alternative pharmacotherapies.…”
Section: Discussionmentioning
confidence: 94%